Survey of Nepali doctors on the perception of climate change and health effects - Pragya Rai; Eva Gauchan; Richa Pradhan; Kabindra M. Shakya (The Journal of Climate Change and Health)
Introduction: Physicians are often the first to witness the health effects of climate change and this allows them a unique platform to advocate for patients’ health. Developing countries are disproportionately impacted by climate change but less is known about the health effects related to climate change in these countries. This survey was done to summarize the observations of Nepali physicians on patients' health as affected by climate change, as well as to assess the need for educational opportunities in the medical community. Methods: An electronic survey on health effects related to climate change and climate change awareness was sent to Nepali physicians by email and social media. Results: Almost all Nepali physician respondents (99%, n = 177) reported climate change is happening, and 67% of respondents mentioned time and 53% of respondents noted knowledge as the main barriers for communicating about climate change with patients. Nepali physicians mentioned training (87%), continuing professional education (85%), health action alerts (84%), patient education materials (84%) and policy statements by professional associations (79%) would be helpful for climate change communication. Conclusion: This survey presents a unique case study describing the health effects of climate change witnessed by physicians in Nepal. This survey highlights that Nepali physicians are keenly aware of the harmful effects of climate change on health, duly acknowledge gaps in education in this topic and report interest in future educational activities to enhance education and to improve their ability to communicate effectively regarding the health impacts of climate change with patients.